Mathematics
pineapplesrock863
26

An equation is shown below: 4(x − 3) − 5(x + 1) = 3 Which statement shows a correct next step in solving the equation? The equation can become 4x − 3 − 5x + 1 = 3 by applying the associative property of multiplication. The equation can become 4x − 3 − 5x + 1 = 3 by applying the distributive property. The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property. The equation can become 4x − 12 − 5x − 5 = 3 by applying the associative property of multiplication

+2
(2) Answers
Anthonybabygirl69

Correct option is C/Third one.

MieshaGum959

I believe correct answer is C as well

Add answer